The Use of Indocyanine Green Fluorescence Angiography in Pediatric Surgery: A Systematic Review and Narrative Analysis - Le-Nguyen, Annie; O'Neill Trudeau, Maeve; Dodin, Philippe; Keezer, Mark R.; Faure, Christophe; Piché, Nelson (Frontiers in Pediatrics, 2021)
Purpose Indocyanine green fluorescence angiography (ICG-FA) is a validated non-invasive imaging technique used to assess tissue vascularization and guide intraoperative decisions in many surgical fields including plastic surgery, neurosurgery, and general surgery. While this technology is well established in adult surgery, it remains sparsely used in pediatric surgery. Our aim was to systematically review and provide an overview of all available evidence on the perioperative use of indocyanine green fluorescence angiography in pediatric surgical patients. Methods We conducted a systematic review with narrative synthesis in conformity with the PRISMA guidelines using PubMed, Medline, All EBM Reviews, EMBASE, PsycINFO, and CINAHL COMPLETE databases to identify articles describing the perioperative use of ICG-FA in pediatric patients. Two independent authors screened all included articles for eligibility and inclusion criteria. We extracted data on study design, demographics, surgical indications, indocyanine green dose, and perioperative outcomes. We developed a risk of bias assessment tool to evaluate the methodological quality of included studies. Results Of 1031 articles retrieved, a total of 64 articles published between 2003 and 2020 were included reporting on 664 pediatric patients. Most articles were case reports and case series (n=36; 56%). No adverse events related to ICG-FA were reported in the included articles. Risk of bias was high. We did not conduct a meta-analysis given the heterogeneous nature of the populations, interventions, and outcome measures. A narrative synthesis is presented. Conclusion Indocyanine green fluorescence angiography is a safe imaging technology and its use is increasing rapidly in pediatric surgical specialties. However, the quality of evidence supporting this trend currently appears low. Case-control and randomized trials are needed to determine the adequate pediatric dose and to confirm the potential benefits of ICG-FA in pediatric surgical patients.